Fundacion Chile Incubator : Chile Case Study - World Bank (Washington, DC, 2014)
Foundation Chile was created in 1976 as a nonprofit governed jointly by the Chilean government and a large American conglomerate. It proactively introduces technology innovations and develops companies in target industries including agribusiness, marine resources, forestry, environment and chemical metrology, human capital, and information and communication technologies. Among its successes have been a new method for packaging beef that enables ranchers to export it more easily, and introducing raspberries, blueberries, oysters and salmon farming for profitable overseas markets.